A 2nd Generation Linkage Map of Heterobasidion annosum s.l. Based on In Silico Anchoring of AFLP Markers - Lind, Mårten; van der Nest, Magriet; Olson, Åke; Brandström-Durling, Mikael; Stenlid, Jan (PLOS ONE, 2012)
In this study, we present a 2nd generation genetic linkage map of a cross between the North American species Heterobasidion irregulare and H. occidentale, based on the alignment of the previously published 1st generation map to the parental genomes. We anchored 216 of the original 308 AFLP markers to their respective restriction sites using an in silico-approach. The map resolution was improved by adding 146 sequence-tagged microsatellite markers and 39 sequenced gene markers. The new markers confirmed the positions of the anchored AFLP markers, fused the original 39 linkage groups together into 17, and fully expanded 12 of these to single groups covering entire chromosomes. Map coverage of the genome increased from 55.3% to 92.8%, with 96.3% of 430 markers collinearly aligned with the genome sequence. The anchored map also improved the H. irregulare assembly considerably. It identified several errors in scaffold arrangements and assisted in reducing the total number of major scaffolds from 18 to 15. This denser, more comprehensive map allowed sequence-based mapping of three intersterility loci and one mating type locus. This demonstrates the possibility to utilize an in silico procedure to convert anonymous markers into sequence-tagged ones, as well as the power of a sequence-anchored linkage map and its usefulness in the assembly of a whole genome sequence.